Risk factors for patellofemoral pain: a systematic review and meta-analysis. Issue 5 (18th March 2019) - Neal, Bradley S; Lack, Simon D; Lankhorst, Nienke E; Raye, Andrew; Morrissey, Dylan; van Middelkoop, Marienke
Abstract : Background: Patellofemoral pain (PFP) is a prevalent condition commencing at various points throughout life. We aimed to provide an evidence synthesis concerning predictive variables for PFP, to aid development of preventative interventions. Methods: We searched Medline, Web of Science and SCOPUS until February 2017 for prospective studies investigating at least one potential risk factor for future PFP. Two independent reviewers appraised methodological quality using the Newcastle–Ottawa Scale. We conducted meta-analysis where appropriate, with standardised mean differences (SMD) and risk ratios calculated for continuous and nominal scaled data. Results: This review included 18 studies involving 4818 participants, of whom 483 developed PFP (heterogeneous incidence 10%). Three distinct subgroups (military recruits, adolescents and recreational runners) were identified. Strong to moderate evidence indicated that age, height, weight, body mass index (BMI), body fat and Q angle were not risk factors for future PFP. Moderate evidence indicated that quadriceps weakness was a risk factor for future PFP in the military, especially when normalised by BMI (SMD −0.69, CI −1.02, –0.35). Moderate evidence indicated that hip weakness was not a risk factor for future PFP (multiple pooled SMDs, range −0.09 to −0.20), but in adolescents, moderate evidence indicated that increased hip abduction strength was a risk factor for future PFP (SMD 0.71, CI 0.39, 1.04). Conclusions: This review identified multiple variables that did not predict future PFP, but quadriceps weakness in military recruits and higher hip strength in adolescents were risk factors for PFP. Identifying modifiable risk factors is an urgent priority to improve prevention and treatment outcomes.